2021
DOI: 10.4314/jasem.v25i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Petrophysical Parameters of Reservoir Sand Wells in Uzot-Field, Onshore Niger Delta Basin, Nigeria

Abstract: Evaluation of the petrophysical parameters in Uzot-field was carried out using Well log data. The target for this study was the D3100 reservoir sand of wells Uz 004, Uz 005, U008 and Uz 011 with depth range of 5540ft to 5800ft across the four wells. Resistivity logs were used to identify hydrocarbon or water-bearing zones and hence indicate permeable zones while the various sand bodies were then identified using the gamma ray logs. The results showed the delineated reservoir units having porosity ranging from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Variation in the depths down hole for each of the methods revealed that shale volume estimates with the Larionov model was determined across thickness 142. reservoirs properties that are needed to clearly determine the actual shale content in the hydrocarbon (HC) reservoirs (Adepehin et al, 2022). This is very essential in estimating accurately, other geophysical (petrophysical) parameters such as water saturation, effective porosity, permeability and Net to Gross thickness which are instrumental and germane in determining the (hydrocarbon) HC potential, quality of reservoirs and realistic estimation of HC reserves (Omoja and Obiekezie, 2021). Estimation of the reservoir shale volume can be done with different models which have been well explained in literatures.…”
Section: Introductionmentioning
confidence: 99%
“…Variation in the depths down hole for each of the methods revealed that shale volume estimates with the Larionov model was determined across thickness 142. reservoirs properties that are needed to clearly determine the actual shale content in the hydrocarbon (HC) reservoirs (Adepehin et al, 2022). This is very essential in estimating accurately, other geophysical (petrophysical) parameters such as water saturation, effective porosity, permeability and Net to Gross thickness which are instrumental and germane in determining the (hydrocarbon) HC potential, quality of reservoirs and realistic estimation of HC reserves (Omoja and Obiekezie, 2021). Estimation of the reservoir shale volume can be done with different models which have been well explained in literatures.…”
Section: Introductionmentioning
confidence: 99%